An enzymatic Finkelstein reaction: fluorinase catalyses direct halogen exchange. Issue 32 (31st July 2019) - Lowe, Phillip T.; Cobb, Steven L.; O'Hagan, David
Abstract : The fluorinase enzyme catalyses a direct displacement of bromide and iodide by fluoride ion from 5′-bromodeoxyadenosine and 5′-iododeoxyadenosine respectively to form 5′-fluorodeoxyadenosine in the absence ofl -methionine or S -adenosyl-l -methionine. Abstract : The fluorinase enzyme from Streptomyces cattleya is shown to catalyse a direct displacement of bromide and iodide by fluoride ion from 5′-bromodeoxyadenosine (5′-BrDA) and 5′-iododeoxyadenosine (5′-IDA) respectively to form 5′-fluorodeoxyadenosine (5′-FDA) in the absence ofl -methionine (l -Met) or S -adenosyl-l -methionine (SAM). 5′-BrDA is the most efficient substrate for this enzyme catalysed Finkelstein reaction.